LABOR ACTIVITY IN EVERYDAY LIFE OF PEOPLE OF KABARDINO-BALKARIA DURING THE GREAT PATRIOTIC WAR (1941-1945) - Tetuev, Alim Inzrelovic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper reviews the experience of the work of state and authorities of Kabardino-Balkaria in organizing the labor activity of workers, collective farmers and employees in the conditions of the approaching front, temporary occupation and the period of restoration of the national economy after the end of the Great Patriotic War (1941-1945). The author analyses the number of workers and employees, including by age and gender in various sectors of the national economy of Kabardino-Balkaria, as well as the reasons for the shortage of labor resources in the region during the years of war. The activity of industrial enterprises of the region for the production of products for civil and military purposes is revealed. The forms of remuneration and taxation of workers and employees are investigated. We note that mandatory non-refundable cash contributions to the Defense Fund and an increase in market prices on collective farm markets led to the factual decrease of wages among workers and employees of the republic. The degree of participation of the population of the republic in the construction of defensive structures, the collection of warm clothes and gifts for the soldiers of the Red Army, the creation of the grain fund of the Red Army and the Defense Fund, and the subscription to State loans is revealed. The methods and techniques of carrying out the labor mobilization of the civilian population in agricultural production in the conditions of the approaching front are considered. The production activity of collective farmers is studied in the context of a new form of wages and an increase in the mandatory minimum of workdays. The reasons for the low labor activity of a part of the rural population in the region are determined. The results of labor and economic mobilization of the population of the republic are summarized.